2013
DOI: 10.1002/cjce.21948
|View full text |Cite
|
Sign up to set email alerts
|

Efficient method for the synthesis of fatty acid amide from soybean oil methyl ester catalysed by modified CaO

Abstract: A new method for the heterogeneous synthesis of ethanolamide from soybean oil methyl ester and monoethanolamine/diethanolamine has been established by using CaO and modified CaO as the solid basic catalyst. As the results show, the commercial CaO catalyst gives a high yield (80.2%) of monoethanolamide with high purity at a ratio of methyl ester to amine of 1: 2 after 3 h under the reaction temperature of 130°C over modified CaO. The yield was greatly enhanced to 96.3% after commercial CaO was modified by benzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 16 publications
1
12
0
1
Order By: Relevance
“…The ratio diethanolamine and oleic acid of 1 and 3 is noted as an optimum results and a good compromise between high conversion and enzyme chemo-selectivity. The observations are in line with Zhang and associates 1 , which concluded that the addition of base through increased amine ratio to the reaction mixture would increase the yield of amidification.…”
Section: Analysis Of the Effect Of The Interaction Variablesupporting
confidence: 90%
See 2 more Smart Citations
“…The ratio diethanolamine and oleic acid of 1 and 3 is noted as an optimum results and a good compromise between high conversion and enzyme chemo-selectivity. The observations are in line with Zhang and associates 1 , which concluded that the addition of base through increased amine ratio to the reaction mixture would increase the yield of amidification.…”
Section: Analysis Of the Effect Of The Interaction Variablesupporting
confidence: 90%
“…Fatty amide is surfactant containing amide bond, where this bond is chemically and physically very stable in alkaline media 1 . This surfactant is a nonionic surfactant and has been developed in the industry because of their emollient and lubricating properties, and low reactivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amide synthesis in literature have been performed under varying reaction conditions, viz., without catalyst 15,19 , in presence of bio 22,29,45 or chemical catalysts 16,20,[30][31][32]41,[46][47][48] . Table 3 present …”
Section: Comparison Of Ni/cao Activity With Few Literature Reported Cmentioning
confidence: 99%
“…[51] For example, asah eterogeneous catalyst, CaO was applied in the amidation of soybean oil. [51] It is, however,k nown that CaO is prone to leaching at high temperature in the presence of fatty acids. [52] In the case of leaching, fatty acids can be saponified;t hus leadingt oh omogeneous catalysis.…”
Section: Amidation Of Different Feedstockmentioning
confidence: 99%